Underwater treadmill training for a greenstick fracture in a collegiate softball player: a case report - Harrison, L. J.; Young, K. L.; Stevens, S. L.; Caputo, J. L. (International Journal of Athletic Therapy & Training, 2017)
A 19-year-old collegiate softball player collided with a fence while trying to catch a fly ball, resulting in a greenstick fibular fracture. Underwater treadmill training (UTT) was used as a modality to supplement traditional physical therapy (TPT). Active range of motion (AROM) in all directions for the knee, hip, and ankle, girth of the thigh and lower leg, static balance, and 6-Minute Walk Test (6MWT) distance were assessed pre- and postintervention. The addition of UTT to TPT led to postintervention increases in AROM, static balance, and limb girth, with no additional discomfort to the participant.